Kajian Kerentanan Gempabumi Gedung Bertingkat Dengan Bentuk Beaturan Dan Tidak Beraturan - Pradono, Mulyo Harris (Jurnal Sains dan Teknologi Indonesia, 2014)
Jakarta as the capital of the country has a lot of buildings. The number of multi-story buildings with a height of more than nine floors reaching more than 700 buildings. Meanwhile, Jakarta is also not free from the threat of earthquakes. According to the Ministry of Public Works, Jakarta was in zoning with moderate seismicity level. However, it does not avoid the possibility of the occurrence of large earthquakes, i.e. to the level of 2500 year earthquake. A seismic level of 500 years of occurrence probability would produce an earthquake tremor in Jakarta as large as that felt in Padang in September 2009, which is around MMI VII to VIII. Therefore, it is necessary to study the vulnerability of high-rise buildings in Jakarta in the face of the threat of earthquakes, so as to assess the level of the risk.Jakarta sebagai ibukota negara memiliki banyak sekali gedung bertingkat. Jumlah gedung bertingkat dengan ketinggian lebih dari sembilan lantai mencapai lebih dari 700 gedung. Sementara itu, Jakarta juga tidak lepas dari ancaman gempabumi. Menurut Kementerian Pekerjaan Umum, Jakarta berada pada zonasi dengan tingkat kegempaan sedang. Namun tidak terhindar dari kemungkinan terjadinya gempabumi besar, yaitu untuk level gempa 2500 tahun. Sedangkan gempa dengan probabilitas kejadian 500 tahun akan menghasilkan gempa tremor di Jakarta sebesar seperti yang dirasakan di Padang pada bulan September 2009, yaitu sekitar MMI VII sampai VIII. Oleh sebab itu, diperlukan kajian kerentanan gedung-gedung bertingkat di DKI Jakarta dalam menghadapi ancaman gempabumi, sehingga dapat diketahui tingkat risikonya.Keywords: multistory building, shape, vulnerability, risk, earthquake